Primary urothelial carcinoma of the prostate: A rare case report. Issue 3 (January 2019) - Zhou, Jun; Yang, Cheng; Lu, Zhaoxiang; Zhang, Li; Yin, Yu; Tai, Sheng; Liang, Chaozhao
Abstract: Rationale: Prostatic urothelial carcinoma is a rare disease. Medical misdiagnosis rates remain high because there are no specific clinical symptoms or imaging features, which decreases patient survival. We report a case of prostatic urethral cancer confirmed by transrectal ultrasound-guided prostate biopsy because of an abnormal digital rectal exam. Patient concerns: A 55-year-old man was referred to our hospital due to lower urinary tract symptoms that lasted for 5 years. Diagnoses and Interventions: On digital rectal examination, a hard and enlarged prostate was detected. Computed tomography, bone scintigraphy, and magnetic resonance imaging indicated benign prostatic hyperplasia. The patient underwent transrectal ultrasound-guided prostate biopsy. From the histopathological examination and immunohistochemical markers, a diagnosis of high-grade prostatic urothelial carcinoma was made. We excluded the possibility of urothelial cancer originating in the bladder lining after transurethral resection of the bladder. Radical cystoprostatectomy was performed, followed by 6 cycles of cisplatin and gemcitabine chemotherapy. Postoperative pathology showed primary urothelial carcinoma of the prostate. Outcomes: The patient recovered smoothly after surgery. After a 6-month follow-up, no evidence of local recurrence or metastatic disease was found. Lessons: This case reminds clinicians that, for middle-aged men with suspicious digital rectal examinations, a diagnosis of prostatic urothelial carcinoma should be considered. Initial radical surgery followed by combination chemotherapy is suggested for therapeutic management.